A Functional Approach to Natural Language - Plojović, Šemsudin; Radu, Bucea-Manea-Ţoniş; Kuleto, Valentin; Beteringhe, Adrian; Ilić P., Milena (Journal of economic development, environment and people, 2022)
This article does not aim to erase the border, rather vague, between natural and artificial languages, but to offer the researcher in the field of language analysis a useful tool for their logical generation and interpretation. After processing the available literature and setting the theoretical framework, a case study was conducted concerning the application of the functional approach in natural languages, and the obtained results indicate the following conclusion: The only difference between functional and natural language is that the condition of interrupting recursive calls may be external to the calling auto function in the case of natural language. Basically, once the message is understood or transmitted, it leaves the loop, this aspect being part of the communication protocol between people.